2014
DOI: 10.1089/ten.tea.2013.0438
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Rat Lungs Retain Hallmarks of Vascular Disease upon Decellularization but Support the Growth of Mesenchymal Stem Cells

Abstract: There are an insufficient number of donor organs available to meet the demand for lung transplantation. This issue could be addressed by regenerating functional tissue from diseased or damaged lungs that would otherwise be deemed unsuitable for transplant. Detergent-mediated whole-lung decellularization produces a threedimensional natural scaffold that can be repopulated with various cell types. In this study, we investigated the decellularization and initial recellularization of diseased lungs using a rat mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 76 publications
1
28
0
1
Order By: Relevance
“…Hence, rather than/in lieu of optimizing the decellularization techniques, replenishment of essential, cell-instructive matricellular ECM components might be an alternative approach for countering ECM loss and improving functional recellularization (52). The general maintenance of the morphology of the lung vascular ECM network following decellularization has been reported, especially for the macrovasculature (10,21,74,83,93,119). As detailed earlier, in intact lung tissue one can utilize histological stains such as Verhoeff's van Gieson, which stains elastic fibers, to identify large diameter arteries from large-diameter veins and airways by the presence of a thick internal elastic lamina in the arteries and its low abundance in the veins and airways (61).…”
Section: Good (Ie Physiological) 1)mentioning
confidence: 94%
See 3 more Smart Citations
“…Hence, rather than/in lieu of optimizing the decellularization techniques, replenishment of essential, cell-instructive matricellular ECM components might be an alternative approach for countering ECM loss and improving functional recellularization (52). The general maintenance of the morphology of the lung vascular ECM network following decellularization has been reported, especially for the macrovasculature (10,21,74,83,93,119). As detailed earlier, in intact lung tissue one can utilize histological stains such as Verhoeff's van Gieson, which stains elastic fibers, to identify large diameter arteries from large-diameter veins and airways by the presence of a thick internal elastic lamina in the arteries and its low abundance in the veins and airways (61).…”
Section: Good (Ie Physiological) 1)mentioning
confidence: 94%
“…Unlike the vessels with diameter greater than 100 m, the structure of small diameter arterioli and venules is similar and difficult to distinguish without highly specific histological techniques (61). Although proteomic analysis of the whole DLS has shown a significant loss of EN (79) following decellularization, histological analysis focused on the vascular compartment suggests that this loss occurs mainly from the airways, pleura, and parenchyma, but not from the vascular compartment: in rodent (21,74,83,93), nonhuman primate (10), and human (119) DLS, the internal elastic lamina of large diameter arteries is maintained. Morphological analysis of the DLS by scanning electron microscopy has shown persistence of hollow tubular structures resembling macrovasculature and, to a lesser extent, also the microvasculature down to the capillary level, thus leaving conduits for blood perfusion largely intact morphologically, yet unable to prevent leakage/hemorrhage (58).…”
Section: Good (Ie Physiological) 1)mentioning
confidence: 99%
See 2 more Smart Citations
“…MSCs within lungs have also been identified that have the ability to express markers of ATI and ATII cells (73,95,214). In this regard, a particularly relevant finding is that MSCs may be less finicky toward the scaffold milieu in terms of attachment (19,21,170,180,213,217). However, what is not yet established is whether MSCs fully redifferentiate into specific lung cell types within a scaffold and recapitulate the functions of the native cell type.…”
Section: Recellularization In Lung Bioengineeringmentioning
confidence: 99%